Thirst for wine? : An amphorae assemblage from Vesuvius and the problem of self-sufficiency in late antique Campania - Ferdinando De Simone, Girolamo; Serena Martucci, Caterina (Rei Cretariae Romanae Fautorum Acta, 2017)
Buried by two eruptions, in AD 79 and 472, the archaeological sites in the environs of Mount Vesuvius have the potential to harvest high-resolution data like the remains of carbonised leaves and ploughing furrows, which can be used alongside with the artefacts to capture a more holistic picture of ancient life and economy at the time of the catastrophes. Within this framework, the amphorae assemblages can illuminate on the trade of some staple food – wine, oil, and salsamenta – and potentially reveal for each of them the degree of dependence of a region on others. In order to do so, proper quantifications are needed but rarely they are carried out even in Pompeii, where the minimum number of individuals (NMI) or the estimated vessel count (EVC) is available only on partial data in just a couple of instances.